Strategies for Developing Religious Literacy in Islamic Education in the Digital Era - Ilyas, Moh; Maknun, Jauhar (Journal of Education and Religious Studies, 2023)
This journal aimed to investigate strategies for developing religious literacy in Islamic education in the digital era. The digital era presents both challenges and opportunities in the dissemination of information and communication. Islamic education must effectively utilize digital media to enhance religious understanding and knowledge. In this journal, the concept of religious literacy, the role of technology in religious education, and strategies that can be implemented to develop religious literacy in the digital era were discussed. This study was conducted using a qualitative study approach through a literature review, utilizing various sources such as books and academic literature as data sources. These sources were read, recorded, and analyzed, leading to the presentation of several strategies in the conclusion aimed at developing religious literacy in Islamic education in the digital era.